Development Of Multiplex Real-Time Reverse Transcription Pcr (qRT-PCR) Assay For Detection And Subtyping Of Avian Influenza Virus - Yee, May Ye (2020)
Avian flu is a serious disease that always give rise to devastated consequences in poultry industry. This disease is caused by influenza A virus bird’s strain. The genome of avian strain of influenza A virus (AIV) exhibits high mutation rate by means of antigenic drift and shift, leading to the emergence of historic pandemics and epidemics. The first line of defence against avian influenza relies on rapid diagnosis. Current singleplex real-time RT-PCR (qRT-PCR) assay is not cost effective and internal control is not included. In this study, an in-house, two-stage multiplex qRT-PCR assay was developed for simultaneous detection and subtyping of H5, H7 and H9 subtype of AIV, the three most common subtypes isolated from poultry.